Good Practice in Pediatric and Adolescent Gynecology (Springer International Publishing, 2018)
This volume focuses on a period in women's lives that is particularly important in the context of preventing major sexual and reproductive diseases. Recommendations by the Italian Society of Pediatric and Adolescent Gynecology, form the basis of this up-to-date and practical book. Experts in the field comprehensively cover all the relevant topics in pediatric and adolescent gynecology, such as pubertal disorders, genital malformations and menstrual cycle disorders. The book will prove a valuable and practice-oriented tool for, gynecologists, pediatricians and endocrinologists, as well as researchers and practitioners interested in the topic.